Trace element, antioxidant and oxidant levels in spinal cord injury: different perspective on the effects of valproic acid - Ulas, M.; Argadal, O. G. (Verduci Publisher, 2023)
OBJECTIVE: One of the most pronounced phenomena of spinal cord injury (SCI) pathology is various changes caused by oxidative stress due to secondary damage. In re-cent years, it has been understood that valproic acid (VPA) has neuroprotective properties other than its clinical effect. The aim of this study is to investigate whether there is a change in antiox-idant activity and trace the element level due to SCI-induced secondary damage, and to examine whether VPA has an effect on this change.MATERIALS AND METHODS: Experimental-ly, spinal damage was induced in a total of six-teen rats by compressing the infrarenal and iliac bifurcation parts of the aorta for 45 minutes and these rats were equally divided into SCI (control) and SCI + VPA groups. The treatment group was injected with VPA (300 mg/kg) intraperitoneally once following SCI. In addition, the motor neuro-logical functions of both groups after SCI were evaluated with the Basso, Beattie, and Bresnah-an (BBB) locomotor rating scale and Rivlin's an-gle of incline test. The spinal cord tissues of both groups were homogenized and the supernatants were separated for biochemical analysis.RESULTS: The results showed that SCI signifi-cantly reduced catalase (CAT), glutathione perox-idase (GPx), total antioxidant status (TAS), mag-nesium (Mg), zinc (Zn) and selenium (Se) levels and increased total oxidative status (TOS), oxida-tive stress indices (OSI), chromium (Cr), iron (Fe), and copper (Cu) in damaged spinal cord tissue. In particular, the administration of VPA prior to the significant increase in the effect of SCI -sec-ondary damage turned these negative findings into positive.CONCLUSIONS: Our findings show that the spinal cord tissue damaged during SCI is pro-tected against oxidative damage thanks to the neuroprotective property of VPA. Furthermore, it is an important finding that this neuropro-tective mechanism contributes to the mainte-nance of the level of essential elements and an-tioxidant activity against SCI-induced second-ary damage.
Keywords: Spinal cord injury; Trace elements; Valproic acid; Oxidative stress; Antioxidant activity